What is the most effective management forH pylorigastritis?. Issue 9 (September 2017) - Lamberton, Nathan; Joseph, Matthew; Wilson, Stephen A.
Abstract : Bottom line : The most effective treatments include 7–14 days of quadruple therapy, 10–14 days of standard triple therapy plus probiotics, and 10–14 days of levofloxacin plus amoxicillin/clarithromycin plus a proton‐pump inhibitor (PPI) (SOR: A, meta‐analyses of RCTs). In areas where resistance to either metronidazole or clarithromycin is >80%, clarithromycin, amoxicillin, metronidazole, and a PPI for 10 days preserves eradication rates (SOR: A, meta‐analysis of RCTs).